Oral and literate traditions - Botha, Pieter J. J. (Koers, 1992)
In this study the importance of research concerning orality and oral traditions for a variety of pressing current issues related to social history, cultural studies, education and science of religion is stressed. It is necessary to take into account the full range of language use as it is spoken and listened to, read and written, to improve our descriptions and analyses of ways of communicating and consequently to uncover the inter-relatedness of language and culture.